Variations for Fusarium head blight resistance associated with genomic diversity in different sources of the resistant wheat cultivar ‘Sumai 3’ - Niwa, Sayaka (Japanese Society of Breeding, 2014)
Fusarium head blight (FHB), caused by Fusarium graminearum, is a serious disease of wheat (Triticum aestivum L.) associated with contamination by the mycotoxin deoxynivalenol (DON). The FHB-resistant wheat cultivar ‘Sumai 3’ has been used extensively around the world. The existence of variation in FHB resistance among ‘Sumai 3’ accessions has been discussed. In this study, genetic variation among ‘Sumai 3’ accessions collected from six countries were identified using SSR markers; our results demonstrate unique chromosome regions in Sumai 3-AUT and Sumai 3-JPN (‘Sumai 3’ accessions from Austria and Japan, respectively). Field evaluation indicated strong resistance to FHB in Sumai 3-AUT. The polymorphic rate (number of polymorphic markers/number of available markers × 100) based on a DArT array was 12.5% between the two ‘Sumai 3’ accessions. Genotyping for DNA markers flanking FHB-resistant quantitative trait loci (QTLs) revealed genetic variations for the QTL regions on 5AS and 2DS; however, no variation was observed for the QTL regions on 3BS and 6B. Thus, the variation in FHB resistance among ‘Sumai 3’ accessions in the field is due to genetic diversity.